A Selenium Containing Inhibitor for the Treatment of Hepatocellular Cancer - Hephzibah Rani S. Tagaram; Dhimant Desai; Guangfu Li; Dai Liu; C. Bart Rountree; Kavitha Gowda; Arthur Berg; Shantu Amin; Kevin F. Staveley-O'Carroll; Eric T. Kimchi (MDPI AG, 2016)
Hepatocellular carcinoma (HCC) is the third most deadly cancer in the world. New treatment strategies are desperately needed due to limited standard therapies. Activation of the Erk, Akt, and STAT3pathways is implicated in the prognosis of HCC. The Se,Se'-1,4-phenylenebis(1,2-ethanediyl) bisisoselenourea (PBISe), is a selenium-containing MAPK and PI3 kinase inhibitor, effectively inhibit tumorigenesis in a variety of experimental models. The aim of our study is to demonstrate the potential role of PBISe in the treatment of HCC. The anti-proliferative and pro-apoptotic ability of PBISe is studied in vitro in four human HCC cell lines and in vivo in a spontaneous murine HCC model. Inhibition of cancer growth was performed by cell viability assay and apoptosis by caspase 3/7, PARP cleavage, annexin-V, and TUNEL assays. Role of PBISe on PI3 kinase, MAPK and STAT3 signaling is determined by Western blotting. In vivo effects of PBISe on tumor sizes were monitored using MRI in a spontaneous murine HCC. Liver tissues from the PBISe-treated mice are analyzed for angiogenesis, proliferation, and signaling pathway markers. Overall, PBISe activated caspase-3/7 and increased DNA fragmentation, which is positively correlated with the increased PARP cleavage. PBISe promoted apoptosis by inhibiting PI3K, MAPK, and STAT3 signaling with significant reduction in the tumor sizes (p < 0.007). PBISe-treated tumors reduced survival marker PCNA, and angiogenesis markers Vegf-A, Vegf-R3 and CD34. These results demonstrate the chemotherapeutic effects of PBISe, by inhibiting tumor growth and facilitating tumor apoptosis for HCC treatment.